2021
DOI: 10.17161/kjm.vol1413771
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Incident Location of Traumatic Injuries at a Single Level I Trauma Center

Abstract: Introduction: Traumatic injuries are preventable and understanding determinants of injury, such as socio-economic and environmental factors, is vital.  This study evaluated traumatic injuries and identified areas of high trauma incidence.                                                                                               Methods:  A retrospective review was conducted of all patients 14 years or older who were admitted with a traumatic injury to a Level I trauma center between 2016 and 2017.  De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Handguns rather than shotgun or semi-automatic have a better survival rate due to continually improving trauma care and single rather than multiple penetrating wounds but still incur a significant burden 22 , 49 , 52 . A study evaluating homicidal gunshot wounds at a single Level 1 trauma center in Kansas found handguns to be the most common weapon of choice in their patients 53 . Another study in a rural Midwest level 1 trauma center performed by Guetschow et al also observed handguns to be the most common weapon type for unintentional firearm related injuries 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Handguns rather than shotgun or semi-automatic have a better survival rate due to continually improving trauma care and single rather than multiple penetrating wounds but still incur a significant burden 22 , 49 , 52 . A study evaluating homicidal gunshot wounds at a single Level 1 trauma center in Kansas found handguns to be the most common weapon of choice in their patients 53 . Another study in a rural Midwest level 1 trauma center performed by Guetschow et al also observed handguns to be the most common weapon type for unintentional firearm related injuries 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Handguns account for most of the rearm related injuries in this retrospective study. A study evaluating homicidal gunshot wounds at a single Level 1 trauma center in Kansas found handguns to be the most common weapon of choice in their patients [13]. Another study in a rural Midwest level 1 trauma center performed by Guetschow et al also observed handguns to be the most common weapon type for unintentional rearm related injuries [14].…”
Section: Discussionmentioning
confidence: 99%